Acquisitions, Node Collapse, and Network Revolution - Hernandez, Exequiel; Menon, Anoop (Management Science, 2018)
We explore a novel mechanism of network change that occurs when a firm acquires another one and inherits its network ties. Such “node collapse” can radically restructure the network in one transaction, constituting a revolutionary change compared with the incremental effect of tie additions and deletions, which have been the focus of prior research. We explore several properties of node collapses: their efficacy in helping firms achieve superior network positions, the externalities they impose on other network actors, and how they provide exclusive control over both internal and network resources. Using a simulation in which actors compete to acquire one another, we model network dynamics driven by node collapses. We find that node collapses directly affect the performance of the acquirer and indirectly that of other actors, and that the direction of network evolution hinges on the degree to which firms pursue internal versus network synergies through node collapses. This paper was accepted by Olav Sorenson, organizations.